PERAN PENDIDIKAN ISLAM DALAM MENANAMKAN NILAI MULTIKULTURAL DI SEKOLAH DASAR - Telaumbanua, Dewi Angreini; Fata, Nahriyah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research aims to describe and analyze the role of Islamic education in instilling multicultural values in the elementary school environment. The method used in this study is a literature study. Along with the increasing social and cultural diversity in Indonesian society, there is a need for mutual respect, tolerance, and inclusivity from an early age for elementary school students. The principles that exist in Islamic education, which are universal, such as justice, brotherhood, and compassion, are very strategic in the face of the formation of a better multicultural character of students. From several relevant literature reviews, this study found that the integration of Islamic values in the curriculum, morality-based learning, and teacher examples play a significant role in the formation of students' multicultural attitudes. From the results of this research, it is hoped that it can contribute to the development of basic education strategies that are responsive to diversity.